The Effect of Artificial Intelligent Technology Used (Duolingo Application) To Enhance English Learning - Baiq Suprapti Handini; Nurhasanah - Nurhasanah; Firdaus Imanl Panly (ELLITE, 2022)
This research aims to figure out the effect of Artificial Intelligence Technology in Duolingo Application to Enhance Speaking and Listening Ability. This study uses a quantitative technique where the researcher conducts experimental research using a quasi-experimental design. This research was completed at Hamzanwadi University with the subjects of this study were all students of second semester with class C English program with a total of 31 students. Where 16 students were the experimental class and 15 students were the control class. The results of the information investigation utilized descriptive statistics in analyzing the data and for hypothesis testing using normality test, homogeneity test, T-test and One Way- ANOVA. The means score for the speaking experimental class is 88.63, then 75.38 for the listening, and for the speaking control class it is 80.53, then 52.13 for the listening. Then with the result of significance (Sig.) 0.000 0.05. In conclusion, that there is an influence by utilizing the Duolingo application to enhance speaking abilities in second semester of Hamzanwadi University in the English Education Study Program for the academic year 2022-2023.